Assessing the Intention to Use Sports Bracelets Among Chinese University Students: An Extension of Technology Acceptance Model With Sports Motivation - Wang, Yi; Zhang, Xiaotian; Wang, Li (Frontiers in Psychology, 2022)
The use of mobile technology such as sports bracelet is gaining popularity as it modifies the ways and process of learning and teaching in college physical education. However, little empirical evidence can be seen in literature to demonstrate crucial factors influencing university students’ acceptance of sports bracelet. Guided by the Technology Acceptance Model, this study hence aimed at explaining university students’ intention to use sports bracelet. 445 university students in China responded to a 19-item survey package. Results indicated that users’ attitudes towards technology and perceived usefulness were significant predictors of intention to use sports bracelet. Meanwhile, users’ intrinsic sport motivation significantly promoted users’ positive attitudes towards this technology, and was significantly influenced by perceived ease of use and perceived usefulness. Implications of the findings were discussed within the context of physical education.